2016
DOI: 10.1080/20473869.2016.1145396
|View full text |Cite
|
Sign up to set email alerts
|

Current understanding of the factors influencing the functional independence of people with cerebral palsy: a review of the literature

Abstract: Background: The variation in functional independence of people with cerebral palsy (CP) allows us to state that there are various factors influencing the development of this independence. Objective: The purpose of this study was to analyze scientific articles focused on the search for factors influencing the functional independence of people with CP in the context of planning the rehabilitation procedures. Methods: The Medline, PubMed, EBSCO, and ScienceDirect electronic databases were searched for articles on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
(93 reference statements)
0
5
0
2
Order By: Relevance
“…Later, the secondary analysis confirmed that GMFCS level was the most significant predictor of restriction in mobility, with BFMF and IQ as significantly contributing variables [4]. Intellectual level often referred to as the educational level or cognitive functional level is one of the personal features listed as possible factors determining the func-tional independence of persons with CP [14]. This may be caused by the association between the number of additional neuroimpairments in the individual child, including the cognitive impairments, and CP type and GMFCS level, because of major brain malformations and/or severe compromise at birth [4,27].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Later, the secondary analysis confirmed that GMFCS level was the most significant predictor of restriction in mobility, with BFMF and IQ as significantly contributing variables [4]. Intellectual level often referred to as the educational level or cognitive functional level is one of the personal features listed as possible factors determining the func-tional independence of persons with CP [14]. This may be caused by the association between the number of additional neuroimpairments in the individual child, including the cognitive impairments, and CP type and GMFCS level, because of major brain malformations and/or severe compromise at birth [4,27].…”
Section: Discussionmentioning
confidence: 92%
“…The characteristics of mobility and self-care, including the independence level, are usually examined only in relation to gross motor abilities or in relation to gross motor and fine manual abilities [5,[8][9][10][11][12]. Besides, the effects of different types of treatment were examined and the factors influencing the development of functional independence in children with CP identified [6,7,13,14]. In other words, DOI: https://doi.org/10.2298/SARH190321077M previous empirical research did not take into account the overall profile of motor abilities of children with CP that, in addition to both gross motor function and manual abilities, includes bimanual fine motor function.…”
Section: Introductionmentioning
confidence: 99%
“…9 Motor impairment and accompanying problems negatively affect children's functional independence and interaction with their environment. 3,10 Although families do not emphasize the effect of urinary problems, these problems negatively affect functional independence and quality of life. 11,12 All groups of the gross motor function of CP have lower urinary tract symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Foram incluídas no estudo 58 crianças com PC espástica, com idade média entre 3 -8 anos, que foram submetidas a realizar as medidas de: GMFCS, para classificar os padrões de deficiência motora em crianças com PC, com base no movimento autoiniciado em posição sentada, transferências e mobilidade, utilizando níveis limitação entre I a V; medida da função motora grossa-88 (GMFM-88), composto por 88 itens com 5 dimensões resultantes no desempenho de 1 a 4 pontos; Inventario de Avaliação Pediátrica de Incapacidade (PEDI), avaliação que determina a capacidade funcional e desempenho de doentes crônicos ou crianças deficientes, essa possui três domínios: habilidades funcionais, assistência do cuidador e funções sociais, com três subescalas cada sendo elas, autocuidado, mobilidade e função social, Escala de Medição de Controle de Tronco (TCMS) que foi realizado enquanto a criança estava sentada em banco sem encosto e base para os pés e, Escala de Comprometimento de Tronco (TIS), realizada com criança sentada em banco com os membros superiores apoiados nas coxas sem suporte nas costas e durante a execução foi mantida a cabeça e o tronco na linha média foi usada para testar o controle de tronco sentado. Na conclusão da pesquisa foi verificado que o controle de tronco prejudica crianças com PC espástica, e que a avaliação do controle de tronco usando o TCMS possibilita informações valiosas em comparação ao TIS Posluszny et al (2016),. realizou uma análise dos artigos focados nos fatores que influenciam na independência das pessoas com paralisia cerebral (PC) no contexto de intervenções por meio de reabilitação, este estudo se trata de uma revisão de literatura.Foram obtidos resultados de pesquisas que abordam as técnicas de reabilitações atuais para pessoas com PC; ferramentas usadas para avaliação funcional de pessoas com PC; fatores que determinam a independência funcional.De acordo com a literatura anterior, os fatores que influenciam a independência funcional de pessoas com PC ainda não foram totalmente exploradas, o presente estudo sugere que a reabilitação deve ser guiada pelo princípio de foco na função, porém não somos capazes de alterar o tipo ou grau de deficiência numa pessoa com PC.…”
unclassified
“…Ao final desta pesquisa foi entendido que a independência funcional é discutida internacionalmente na literatura cientifica e muitos fatores a influenciam em pessoas com PC. Para o melhor planejamento de reabilitação faz se necessário a qualificação de profissionais diretamente relacionados com pessoas com PC(POSLUSZNY et al, 2016).…”
unclassified